Efeito do sorbet de açaí sobre a mudança de cor de dentes bovinos durante o clareamento com peróxido de carbamida a 10%: estudo in situ e ex-vivo - Pandolfo, Silvia (2023)
Objective This study evaluated the effect of açaí sorbet on the color change of bovine teeth during bleaching with 10% carbamide peroxide at different times. This is an in situ and ex-vivo crossover and randomized study of 3 phases of 14 days each and 7 days of washout. Methods Twelve volunteers used intraoral appliances (AIO) containing 4 samples of bovine enamel (selected by the variable L*) and were randomized (with the same allocation rate) into 3 treatment groups (n=12): bleaching and staining challenge with distilled water, (CA), bleaching and challenge with açaí sorbet (CS), and without bleaching and challenge with açaí sorbet (sCS). Whitening (10% carbamide peroxide) was carried out in situ for 2 hours, the AIO was washed under running water and remained in the mouth for 1 hour. Then, the exvivo staining challenge was performed (immersing the AIO in 5 mL of the solution for 10 minutes). The AIO was removed, washed under running water, brushed, and remained in the mouth until the next day. The ordinates L*, a* and b* (CIELa*b*) were analyzed with a spectrophotometer at baseline (T0) and on days 7 (T7), 15 (T15) and 30 (T30). Data were analyzed by two-way Analysis of Variance (ANOVA) and repeated measures Analysis of Variance. The Tukey Test was used for individual comparisons. Results The results showed that the CA control group did not present L* values compatible with those expected for bleaching, invalidating the other results. Conclusion No conclusions can be made about the effect of açaí during whitening.